Liquid-liquid equilibria of ternary (water + short-chain alcohol + organic solvent) systems - Desrosiers, Isabelle Grace (Stellenbosch : Stellenbosch University, 2025)
Desrosiers, Isabelle Grace. 2024. Liquid-liquid equilibria of ternary (water + short-chain alcohol + organic solvent) systems. Stellenbosch: Stellenbosch Univeristy [online]. Available: https://scholar.sun.ac.za/handle/10019.1/131638